“É uma tempestade que vem destruindo tudo”: o uso de psicotrópicos e o sofrimento psíquico segundo mulheres assistidas por um serviço de atenção primária à saúde - Braga, Raissa de Brito (2020)
Primary Health Care (PHC) is responsible for the most frequent basic health care of the population, with women being a large part of the population served. Among the care developed in PHC, there are mental health care, with the prescription of psychotropic drugs and psychotherapy being the two most common therapies. Given this question, the general objective of this research was to know the experience of women who use psychotropic medications in relation to their health and their affective relationships, and its three specific objectives: To identify, in the women's life trajectory, at what time or situation of the his personal history the psychotropic medication was introduced and what reasons justified the need for this use; Identify if there was and what information was received by women regarding the effects that these drugs can have on the life of each one of them; Understand the consequences of using medications in the lives of these women, from daily activities to their affective relationships. This is a qualitative and descriptive study in which 10 women who were waiting for care in a Basic Health Unit in a municipality in the state of Minas Gerais, over 18 years of age, took part in psychotropic medication for at least six months from the date of the invitation. After accepting and signing the informed consent form to participate in the research, an individual and group interview was conducted and, in addition, the researcher prepared a field diary. After the field phase ended, all audio recordings of the interviews were transcribed for reading and content analysis, together with the field diary produced by the researcher. The age of the participants ranged from 37 to 71 years and five were divorced, four were married and one was single. In addition, only one of them lived alone, while the vast majority shared the house with at least one of the children or their partner. The women's life trajectories were marked by the use of psychotropic medications based on diagnoses of fibromyalgia, depression or insomnia. In the process, five women said they had received information about medications related only to the side effects they might experience on the body and four about the function of the drug in their body. The drugs caused nausea, vomiting and drowsiness, but they were also positive for relieving and treating fibromyalgia pain, suicidal thoughts and insomnia. In addition to medication, psychotherapy was also an important resource in view of the overload of domestic tasks and the functions of caregivers, which led to fatigue and illness. Finally, it was seen that the activities developed in the health unit maintained the traditional clinical forms of care based on individual and medication care. These same data were found in the academic literature, in addition to the difficulty of PHC in dealing with violence against women as a public health issue, since it also appeared in the speech of the interviewees who highlighted the psychological, physical and patrimonial violence suffered in ex-relationships loving. These questions demonstrate the need to develop more research and health practices linked to gender issues linked to socioeconomic and racial issues that interfere in women's lives and health.